Penafsiran Sufistik Makna Khasyyatullah dalam Al-Qur'an - Eko Zulfikar (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
In this millennial era, there has been a lot of moral decadence in society, whether it is done by the young or old age. This is the result of the lack of fear of Allah (hasyyatullah). This paper attempts to explore the meanings of khasyyatullah in the Qur’an. The interpretation is based on the Sufi interpretation books by Ibn ‘Arabi, al-Qusyairi, al-Alusi, al-Tustari, Sa'id Hawwa and Hamka. By using the thematic method and the contextual approach, it was concluded that: the meaning of khasyyatullah in the perspective of Sufistic interpretation is the feeling of a servant to God who has high faith so that it requires him to always fear God. The Qur’an specifies the owners of this khashyatullah to the ulama’, those who know the greatness and power of Allah. With the existence of khasyyatullah, a person will always renew repentance, fight lust, doing good deeds, establish social ties, and revive a more prosperous mosque. Therefore, efforts to create a harmonious society to always be taqarrub to God can be achieved through a khasyyatullah attitude.